Super-toughness Fe-P-C amorphous soft magnetic alloy ribbon and preparation method thereof
By optimizing the composition and preparation process of the thin strip of Fe-P-C amorphous soft magnetic alloy, the shortcomings of the existing Fe-P-C alloy in terms of magnetic induction strength, brittleness and cost are solved, and high saturation magnetic induction strength and excellent plastic toughness are achieved. , improving its application potential in the industrial field.
Patent Information
- Application Number
- CN202411367336.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-01-03
AI Technical Summary
The existing Fe-P-C-based amorphous alloys have shortcomings in magnetic induction strength, material brittleness and cost, which limits their application potential in the industrial field.
The composition of the thin strip of Fe-P-C amorphous soft magnetic alloy is FexPyCz, 82
It significantly improves the saturated magnetic induction strength of the alloy to 1.60~1.68 T, reduces costs, optimizes the heat treatment process, avoids material embrittlement, achieves lower coercivity and excellent plastic toughness, and enhances the competitiveness of the alloy and Application prospects.
Smart Images

Figure CN119243058A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of amorphous alloy materials, and in particular relates to a super-tough Fe-PC series amorphous soft magnetic alloy thin strip and a preparation method thereof. Background Art
[0002] Compared with traditional silicon steel power transformers, transformers made of iron-based amorphous materials have shown remarkable performance in energy efficiency. This significant advantage is due to the unique magnetic properties of amorphous alloys, including extremely low coercivity ( H c ), ultra-high saturation magnetic induction intensity ( B s ), efficient effective magnetic permeability ( µ e ) and significantly reduced energy loss. However, many current iron-based amorphous alloy formulas incorporate a high proportion of non-magnetic amorphous forming elements, such as Al, Ga, Nb, Mo, Y, etc. The introduction of these elements weakens the magnetic properties of the alloy to a certain extent; on the other hand, it inevitably increases the manufacturing cost of the material.
[0003] At present, the chemical composition of the widely used amorphous soft magnetic material 1K101 is based on Fe, Si, and B as the core elements, and incorporates trace alloying elements such as Cu, Ni, and Mo. However, in terms of technical specifications, the saturation magnetic induction intensity of this material is 1.32~1.56 T, which is slightly insufficient compared to similar products of Allied Company in the United States. In addition, the domestic 1K101 amorphous soft magnetic material also faces challenges such as significant brittleness, insufficient toughness, and limited processing performance. These factors jointly restrict its potential for widespread application in the industrial field. Therefore, it is particularly urgent and important to develop a new type of amorphous soft magnetic alloy that is low-cost, has excellent plasticity and toughness, and has good thermal stability.
[0004] In addition to the traditional Fe-Si-B system, Fe-PC amorphous alloys also show excellent soft magnetic properties. For example, Fe 75 P 15 C 10 alloy( PK Rastogi and P Duwez, Journal of Non-Crystalline Solids, 1970, 5:1-16 ), Fe studied by Masumoto et al. in 1975 80 P 15 C5 alloy ( T Masumoto and H Kimura, Journal of the Japan Institute of Metals and Materials, 1975, 39(3):273-280 ) and Fe studied by Wang et al. in 2011 80 P 11 C9 alloy ( JF Wang, R Li, et al. Scripta Materialia, 2011, 65(6):536-539However, for existing Fe-PC amorphous alloys, the Fe content is usually controlled at 80 at.% or lower. B s The value is between 1.31 and 1.56 T. H c The value is between 3.3~16.4 A / m.
[0005] Therefore, the development of a new iron-based amorphous alloy with a simpler composition, excellent magnetic properties and industrial cost-effectiveness will further promote the improvement of transformer energy efficiency and lay a solid foundation for realizing green and low-carbon energy conversion and transmission systems. Summary of the invention
[0006] In view of the deficiencies of Fe-PC amorphous alloy materials in the prior art in terms of magnetic induction intensity, material brittleness and cost, the present invention provides a super-tough Fe-PC amorphous soft magnetic alloy strip and a preparation method thereof. This Fe-PC amorphous soft magnetic alloy strip not only has higher saturation magnetic induction intensity, but also has good plasticity and toughness, and also has obvious advantages in cost-effectiveness.
[0007] The present invention is achieved through the following technical solutions: A super-tough Fe-PC amorphous soft magnetic alloy ribbon, wherein the Fe-PC amorphous soft magnetic alloy ribbon is composed of Fe x P y C z , x, y, z represent the atomic percentage of each element, 82<x<85, 8<y<12, 5<z<7, and x+y+z=100.
[0008] Further, 82.5≤x≤84.
[0009] Furthermore, the Fe x P y C z Fe 82.5 P 11.5 C6, Fe 83 P 11 C6, Fe 83.5 P 11 C6 or Fe 84 P 10.7 C 5.3 . Furthermore, the thickness of the Fe-PC amorphous soft magnetic alloy strip is 23-26 μm.
[0010] In the present invention, the method for preparing the super-tough Fe-PC amorphous soft magnetic alloy thin strip comprises the following steps: (1) According to Fe x Py C z Make the batch with the ingredients shown; (2) The ingredients in step (1) are melted in an argon protective atmosphere, and after cooling, a master alloy ingot is obtained. The oxide scale on the surface is removed and the master alloy ingot is cut into pieces.
[0011] (3) The spin-quenched alloy ribbon was prepared by single-roll rapid quenching method under argon atmosphere; (4) The spin-quenched alloy ribbon prepared in step (3) is subjected to vacuum annealing treatment at a temperature of 307-317° C. for a holding time of 10-15 min to obtain an ultra-tough Fe-PC amorphous soft magnetic alloy ribbon.
[0012] Furthermore, the ingredients described in step (1) are Fe, Fe3P and C.
[0013] Furthermore, in step (2), the smelting temperature is 1500-2000°C, and the smelting time is 15-20 min.
[0014] Furthermore, the single-roller rapid quenching method in step (3) is operated as follows: a small piece of master alloy ingot is placed in a quartz tube for melting, and the molten metal is sprayed onto the surface of a high-speed rotating copper roller to rapidly cool it to obtain an alloy strip.
[0015] Furthermore, the injection pressure was 0.02 MPa, the linear velocity of the copper roller surface was 40 m / s, and a small hole with a diameter of 0.7-0.8 mm was opened at the lower end of the quartz tube.
[0016] Furthermore, the vacuum annealing temperature in step (4) is lower than the initial crystallization temperature of the amorphous alloy, ensuring that the amorphous structure of the alloy strip is maintained while removing the internal stress.
[0017] Generally speaking, as the Fe content increases, the B s It will increase, but it will also cause a decrease in the glass-forming ability, especially when the Fe content (or the total content of magnetic elements) exceeds 80 at / %, it is difficult for the iron-based amorphous alloy to have a strong glass-forming ability. In a specific embodiment, the Fe content is 82.5-84 at.%, and when the Fe content is lower than 82.5 at.%, B sThe value usually does not exceed 1.60 T; when the Fe content exceeds 84 at.%, the amorphous forming ability of the alloy system will be significantly reduced, and a completely amorphous alloy cannot be prepared. P and C, as amorphous forming elements, play a key role in the alloy. Specifically, the P content is between 8 and 12 at.%, which not only promotes the amorphous forming ability of the alloy, but also improves the initial magnetic permeability of the alloy. The C content is controlled at 5 to 7 at.%, which helps to optimize the soft magnetic properties of the alloy and effectively reduce its coercive force.
[0018] Beneficial effects achieved by the present invention: (1) The alloy components of the present invention are simple and efficient, which not only ensures the amorphous forming ability but also optimizes the soft magnetic properties of the alloy. Only P and C are used as metalloid elements, avoiding the use of high-cost elements such as niobium, thereby significantly reducing the cost. At the same time, the iron content is increased to more than 82 at.%, which effectively improves the alloy. B s, reaching 1.60~1.68 T, which is not only significantly better than traditional iron-based alloys such as SENNTIX ( B s = 1.30 T)、MG2605SA1( B s = 1.56 T), 24KCP ( B s = 1.50 T), YCP-1 ( B s = 1.60 T), METGLAS 2605SC ( B s = 1.60 T) and FINEMET ( B s =1.24 T), which also provides strong support for its competitiveness in the market.
[0019] (2) The present invention has achieved an important breakthrough in the heat treatment process. Compared with the current conventional process, the required temperature is reduced by 5% to 10%, and the processing time is also shortened by 60%; this improvement effectively avoids the problem of material embrittlement that may be caused by high-temperature annealing. By precisely controlling the annealing process at a lower temperature in a short time, the amorphous structure of the material is retained and the internal stress of the alloy strip is successfully eliminated; this optimized treatment ensures that the amorphous alloy strip does not crystallize, thereby achieving a lower coercive force, H c 4.0~8.0 A / m.
[0020] (3) The preparation method of the Fe-PC amorphous alloy ribbon described in the present invention is simple and endows the material with excellent soft magnetic properties and good plastic toughness. Under the conditions that the magnetic flux density is set to 0.5 T and the magnetization frequency is 50 Hz, the iron loss range of the Fe-PC amorphous alloy ribbon sample in the present invention is 0.358~1.525 W / kg. As an amorphous soft magnetic alloy with excellent comprehensive performance, it is expected to replace traditional materials such as silicon steel sheets in the fields of electronics and power, showing broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The spin-quenched Fe-PC alloy strips prepared in Examples 1 to 4 and the spin-quenched Fe-PC alloy strips prepared in Comparative Example 1 are shown in FIG. 82 P 11.7 C 6.3 XRD pattern of alloy ribbon; Figure 2 The spin-quenched Fe-PC alloy strips prepared in Examples 1 to 4 and the spin-quenched Fe-PC alloy strips prepared in Comparative Example 1 are shown in FIG. 82 P 11.7 C 6.3 DSC curve of alloy ribbon; Figure 3 The ultra-tough Fe-PC system (Fe 83 P 11 C6) Bending diagram of amorphous soft magnetic alloy ribbon; 3a, bending appearance; 3b, scanning electron microscope image of the shear band at the bend; Figure 4 The spin-quenched Fe prepared in Comparative Example 2 85 Transmission electron microscopy image of P9C6 alloy ribbon. DETAILED DESCRIPTION
[0022] The above contents of the present invention are further described in detail below through examples, but this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples, and all technologies implemented based on the above contents of the present invention belong to the scope of the present invention.
[0023] Example 1 Fe 82.5 P 11.5 Preparation of C6 super-tough Fe-PC amorphous soft magnetic alloy ribbon: (1) Batching: Convert the atomic percentage into mass percentage according to the alloy composition expression and accurately weigh pure Fe, pure C and Fe3C alloy; (2) Melting and casting: The ingredients in step (1) are placed in an induction melting furnace for melting. Before melting, the vacuum degree is reduced to 3.0 × 10 -3Pa, then close all valves and fill with high-purity argon (purity 99.99%) for smelting, the smelting temperature is 1800 ℃, the smelting time is 20 min, and the master alloy ingot is obtained after cooling. The surface of the master alloy ingot is polished with sandpaper to remove the oxide scale, and then placed in alcohol for ultrasonic cleaning for 10 minutes, blown dry and cut into small pieces of about 3 g for standby use; (3) Preparation of spin-quenched alloy ribbons: Under the protection of argon, a single-roller spinning machine VF-RQT50 produced by Makabe Co., Ltd. of Japan was used for the operation. The small pieces of master alloy ingots were placed in a cleaned quartz tube with a small hole at the bottom. The diameter of the small hole was 0.7 mm. The quartz tube was fixed in the middle of the induction coil, and the distance from the nozzle at the bottom of the quartz tube to the surface of the copper roller was adjusted. Then, the vacuum chamber was evacuated to 7×10 -3 Pa, and after reaching the required vacuum degree, high-purity argon gas is filled into the furnace chamber; the alloy is heated and melted by high-frequency induction heating equipment, and after the alloy liquid is melted for a certain period of time, the molten alloy liquid is sprayed onto the surface of the high-speed rotating copper roller using high-purity argon gas, the spray pressure is 0.02 MPa, and the surface linear speed of the copper roller is 40 m / s, thereby obtaining a continuous alloy thin strip with a thickness of 23 μm; (4) Preparation of ultra-tough amorphous soft magnetic alloy ribbon: The alloy ribbon prepared in step (3) was subjected to vacuum annealing at a temperature of 316 °C for 10 min and 15 min, respectively. After the annealing process was completed, the alloy ribbon was air-cooled to room temperature to obtain an ultra-tough Fe-PC system (Fe 82.5 P 11.5 C6) Amorphous soft magnetic alloy strip.
[0024] Example 1: Spin-quenched Fe 82.5 P 11.5 The X-ray diffraction (XRD) pattern of C6 alloy ribbon is shown in Figure 1 As shown, it has a single amorphous structure; its DSC diagram is shown in Figure 2 As shown, the results showed that Fe 82.5 P 11.5 The C6 amorphous alloy has no obvious glass transition, only two exothermic peaks related to the two-stage crystallization reaction appear; after testing, the spin-quenched Fe 82.5 P 11.5 Curie temperature of C6 alloy ribbon T c The initial crystallization temperature is 580 K. T x 675 K ( Figure 2 ). In addition, the spin-quenched Fe 82.5 P 11.5 The C6 alloy ribbon exhibits good bending toughness and high hardness (724 Hv). The vibrating sample magnetometer (VSM) and DCB - H Analyzer for annealed super-tough Fe 82.5 P 11.5 The magnetic properties of C6 amorphous soft magnetic alloy ribbon were tested, and the results showed that the saturation magnetic induction intensity of the alloy B s 1.61-1.66 T, coercivity H c· is 4.0 A / m, initial magnetic permeability μ i It is 8800~9500 (Table 1).
[0025] Example 2 Fe 83 P 11 Preparation of C6 super-tough Fe-PC amorphous soft magnetic alloy ribbon: (1) Batching: Convert the atomic percentage into mass percentage according to the alloy composition expression and accurately weigh pure Fe, pure C and Fe3C alloy; (2) Melting and casting: The ingredients in step (1) are placed in an induction melting furnace for melting. Before melting, the vacuum degree is reduced to 3.0 × 10 -3 Pa, then close all valves and fill with high-purity argon (purity 99.99%) for smelting, the smelting temperature is 1800 ℃, the smelting time is 20 min, and the master alloy ingot is obtained after cooling. The surface of the master alloy ingot is polished with sandpaper to remove the oxide scale, and then placed in alcohol for ultrasonic cleaning for 10 minutes, blown dry and cut into small pieces of about 3g for standby use; (3) Preparation of spin-quenched alloy ribbons: Under the protection of argon, a single-roller spinning machine VF-RQT50 produced by Makabe Co., Ltd. of Japan was used for the operation. The small pieces of master alloy ingots were placed in a cleaned quartz tube with a small hole at the bottom. The diameter of the small hole was 0.7 mm. The quartz tube was fixed in the middle of the induction coil, and the distance from the nozzle at the bottom of the quartz tube to the surface of the copper roller was adjusted. Then, the vacuum chamber was evacuated to 7×10 -3 Pa, and after the required vacuum degree is reached, high-purity argon gas is filled into the furnace chamber; the alloy is heated and melted by a high-frequency induction heating device, and after the alloy liquid is melted for a certain period of time, the molten alloy liquid is sprayed onto the surface of a high-speed rotating copper roller using high-purity argon gas, the spray pressure is 0.02 MPa, and the surface linear speed of the copper roller is 40 m / s, thereby obtaining a continuous alloy thin strip with a thickness of 23 μm; (4) Preparation of super-tough amorphous soft magnetic alloy ribbon: The alloy ribbon prepared in step (3) was subjected to vacuum annealing at a temperature of 315°C for 10 min and 15 min, respectively. After the annealing process was completed, the alloy ribbon was air-cooled to room temperature to obtain a super-tough Fe-PC system (Fe83 P 11 C6) Amorphous soft magnetic alloy strip.
[0026] Example 2: Spin-quenched Fe 83 P 11 The XRD pattern of C6 alloy ribbon is shown in Figure 1 As shown, it has a single amorphous structure; its DSC diagram is shown in Figure 2 As shown, the results showed that Fe 83 P 11 The C6 amorphous alloy has no obvious glass transition, only two exothermic peaks related to the two-stage crystallization reaction appear; after testing, the spin-quenched Fe 83 P 11 Curie temperature of C6 amorphous soft magnetic alloy ribbon T c is 579 K, the initial crystallization temperature T x 670 K ( Figure 2 ). In addition, the spin-quenched Fe 83 P 11 The C6 alloy ribbon exhibits good bending toughness and high hardness (708 Hv). B - H Analyzer for annealed super-tough Fe 83 P 11 The magnetic properties of C6 amorphous soft magnetic alloy ribbon were tested, and the results showed that the saturation magnetic induction intensity of the alloy B s 1.67-1.68T, coercivity H c 4.3~4.7 A / m, initial magnetic permeability μ i It is 9300~10300 (Table 1).
[0027] Example 2: Super tough Fe 83 P 11 The morphology of the C6 amorphous soft magnetic alloy ribbon after bending is shown in the figure Figure 3 As shown in a, the alloy strip can be bent into a polygon without breaking, which verifies that it still maintains excellent bending ductility after annealing; the shear band near the crease is observed by scanning electron microscopy, and the results are shown in Figure 3 As shown in Figure 2b, the alloy has good ductility during bending. The ductility of amorphous alloys is affected by the amount of free volume and the atomic packing density. For small solute atoms, such as C and P, the size mismatch between them and Fe atoms can be as high as 61% and 14%. The study revealed that larger and smaller atoms can form a densely packed atomic structure, which is extremely beneficial to the ductility of Fe-PC amorphous alloy ribbons.
[0028] Example 3 Fe 83.5 P 10.5 Preparation of C6 super-tough Fe-PC amorphous soft magnetic alloy ribbon: (1) Batching: Convert the atomic percentage into mass percentage according to the alloy composition expression and accurately weigh pure Fe, pure C and Fe3C alloy; (2) Melting and casting: The ingredients in step (1) are placed in an induction melting furnace for melting. Before melting, the vacuum degree is reduced to 3.0 × 10 -3 Pa, then close all valves and fill with high-purity argon (purity 99.99%) for smelting, the smelting temperature is 1800 ℃, the smelting time is 20 min, and the master alloy ingot is obtained after cooling. The surface of the master alloy ingot is polished with sandpaper to remove the oxide scale, and then placed in alcohol for ultrasonic cleaning for 10 minutes, blown dry and cut into small pieces of about 3 g for standby use; (3) Preparation of spin-quenched alloy ribbons: Under the protection of argon, a single-roller spinning machine VF-RQT50 produced by Makabe Co., Ltd. of Japan was used for the operation. The small pieces of master alloy ingots were placed in a cleaned quartz tube with a small hole at the bottom. The diameter of the small hole was 0.7 mm. The quartz tube was fixed in the middle of the induction coil, and the distance from the nozzle at the bottom of the quartz tube to the surface of the copper roller was adjusted. Then, the vacuum chamber was evacuated to 7×10 -3 Pa, and after the required vacuum degree is reached, high-purity argon gas is filled into the furnace chamber; the alloy is heated and melted by a high-frequency induction heating device, and after the alloy liquid is melted for a certain period of time, the molten alloy liquid is sprayed onto the surface of a high-speed rotating copper roller using high-purity argon gas, the spray pressure is 0.02 MPa, and the surface linear speed of the copper roller is 40 m / s, thereby obtaining a continuous alloy thin strip with a thickness of 23 μm; (4) Preparation of ultra-tough amorphous soft magnetic alloy ribbon: The alloy ribbon prepared in step (3) was subjected to vacuum annealing at a temperature of 314 °C for 10 min and 15 min, respectively. After the annealing process was completed, the alloy ribbon was air-cooled to room temperature to obtain an ultra-tough Fe-PC system (Fe 83.5 P 10.5 C6) Amorphous soft magnetic alloy strip.
[0029] Example 3: Spin-quenched Fe 83.5 P 10.5 The XRD pattern of C6 alloy ribbon is shown in Figure 1 As shown, it has a single amorphous structure; its DSC diagram is shown in Figure 2 As shown, the results showed that Fe 83.5 P 10.5The C6 amorphous alloy has no obvious glass transition, only two exothermic peaks related to the two-stage crystallization reaction appear; after testing, the spin-quenched Fe 83.5 P 10.5 Curie temperature of C6 amorphous soft magnetic alloy ribbon T c The initial crystallization temperature is 577 K. T x 658 K ( Figure 2 ). In addition, the spin-quenched Fe 83.5 P 10.5 The C6 alloy ribbon exhibits good bending toughness and high hardness (686 Hv). B - H Analyzer for annealed super-tough Fe 83.5 P 10.5 The magnetic properties of C6 amorphous soft magnetic alloy ribbon were tested and the results showed that the alloy B s 1.66T, H c 4.2~4.9 A / m, μ i It is 6800~8200 (Table 1).
[0030] Example 4 Fe 84 P 10.7 C 5.3 Preparation of ultra-tough Fe-PC amorphous soft magnetic alloy ribbon: (1) Batching: Convert the atomic percentage into mass percentage according to the alloy composition expression and accurately weigh pure Fe, pure C and Fe3C alloy; (2) Melting and casting: The ingredients in step (1) are placed in an induction melting furnace for melting. Before melting, the vacuum degree is reduced to 3.0 × 10 -3 Pa, then close all valves and fill with high-purity argon (purity 99.99%) for smelting, the smelting temperature is 1800 ℃, the smelting time is 20 min, and the master alloy ingot is obtained after cooling. The surface of the master alloy ingot is polished with sandpaper to remove the oxide scale, and then placed in alcohol for ultrasonic cleaning for 10 minutes, blown dry and cut into small pieces of about 3 g for standby use; (3) Preparation of spin-quenched alloy ribbons: Under the protection of argon, a single-roller spinning machine VF-RQT50 produced by Makabe Co., Ltd. of Japan was used for the operation. The small pieces of master alloy ingots were placed in a cleaned quartz tube with a small hole at the bottom. The diameter of the small hole was 0.7 mm. The quartz tube was fixed in the middle of the induction coil, and the distance from the nozzle at the bottom of the quartz tube to the surface of the copper roller was adjusted. Then, the vacuum chamber was evacuated to 7×10 -3Pa, and after the required vacuum degree is reached, high-purity argon gas is filled into the furnace chamber; the alloy is heated and melted by a high-frequency induction heating device, and after the alloy liquid is melted for a certain period of time, the molten alloy liquid is sprayed onto the surface of a high-speed rotating copper roller using high-purity argon gas, the spray pressure is 0.02 MPa, and the surface linear speed of the copper roller is 40 m / s, thereby obtaining a continuous alloy thin strip with a thickness of 23 μm; (4) Preparation of ultra-tough amorphous soft magnetic alloy ribbon: The alloy ribbon prepared in step (3) was subjected to vacuum annealing at a temperature of 308 °C for 10 min and 15 min, respectively. After the annealing process was completed, the alloy ribbon was air-cooled to room temperature to obtain an ultra-tough Fe-PC system (Fe 84 P 10.7 C 5.3 ) Amorphous soft magnetic alloy strip.
[0031] Example 4: Spin-quenched Fe 84 P 10.7 C 5.3 The XRD pattern of the alloy strip is shown in Figure 1 As shown, it has a single amorphous structure; its DSC diagram is shown in Figure 2 As shown, the results showed that Fe 84 P 10.7 C 5.3 The amorphous alloy has no obvious glass transition, and only two exothermic peaks related to the two-stage crystallization reaction appear. 84 P 10.7 C 5.3 Curie temperature of amorphous soft magnetic alloy ribbon T c is 571 K, the initial crystallization temperature T x is 649 K (Table 1). In addition, the spin-quenched Fe 84 P 10.7 C 5.3 The gold ribbon exhibits good bending toughness and high hardness (670 Hv). B - H Analyzer for annealed super-tough Fe 84 P 10.7 C 5.3 The magnetic properties of amorphous soft magnetic alloy strips were tested, and the results showed that the alloy B s 1.60-1.63T, H c 7.2~7.4 A / m, μ i It is 2600~2800 (Table 1).
[0032] Comparative Example 1 The spin-quenched Fe prepared according to the method of Example 1 82 P 11.7 C 6.3 The XRD pattern of the alloy strip is shown in Figure 1 As shown in Figure 2, it has a single amorphous structure; DSC Figure 2 As shown, the results showed that Fe 82 P 11.7 C 6.3 Amorphous alloys have no obvious glass transition, but only two exothermic peaks related to the two-stage crystallization reaction. B - H Analyzer for annealed Fe 82 P 11.7 C 6.3 The magnetic properties of amorphous soft magnetic alloy strips were tested, and the results showed that the alloy B s 1.59~1.60 T, H c 4.0~4.3 A / m, μ i is 8000~8100 (Table 1). That is to say, when the Fe content is lower than 82.5 at.%, the alloy material B s It is difficult to reach above 1.60 T.
[0033] Comparative Example 2 The spin-quenched Fe 85 The transmission electron microscope image of P9C6 alloy ribbon is as follows Figure 4 As shown by Figure 4 It can be seen that the spin-quenched Fe 85 The structural characteristics of the P9C6 alloy ribbon are a small amount of uneven crystal clusters scattered on the amorphous substrate. This is mainly due to the high iron content, which is close to the limit of forming a single amorphous phase. The uneven existence of crystal clusters leads to an increase in the coercivity of the material, which in turn affects the overall magnetic properties of the material. B - H The analyzer is used for annealed Fe 85 P9C6 alloy strips were tested for magnetic properties. H c It is 25.1~26.2 A / m, which indicates that once the Fe content exceeds 85 at.%, it is difficult to effectively reduce the coercivity of the alloy material by conventional annealing process alone.
[0034] The magnetic properties of the super-tough Fe-PC amorphous soft magnetic alloy ribbons prepared in Examples 1 to 4 and the alloy ribbons prepared in Comparative Examples 1 to 2 are shown in Table 1 below: Table 1 Magnetic properties of the super-tough Fe-PC amorphous soft magnetic alloy ribbons prepared in Examples 1 to 4 and the alloy ribbons prepared in Comparative Examples 1 to 2 As shown in Table 1, the Fe 82 P 11.7 C 6.3 Alloy B s The value does not exceed 1.60 T. However, the example samples with an iron content exceeding 82 at.%, including Fe 82.5 P 11.5 C6, Fe 83 P 11 C6, Fe 83.5 P 11 C6 and Fe 84 P 10.7 C 5.3 , their B s The values are all higher than 1.60 T, indicating that the ultra-tough Fe-PC amorphous soft magnetic alloy ribbon of the present invention has B s The performance is better than the control example. Further comparison with other commercial Fe-based amorphous / nanocrystalline alloys on the market, such as SENNTIX ( B s = 1.30 T)、MG2605SA1 ( B s = 1.56 T)、24KCP ( B s = 1.50 T), YCP-1 ( B s = 1.60 T)、METGLAS 2605SC( B s = 1.60 T) and FINEMET ( B s = 1.24 T), it can be seen that Fe 82.5 P 11.5 C6, Fe 83 P 11 C6 and Fe 83.5 P 11 C6 amorphous alloy exhibits higher B s In addition, the Fe prepared in Comparative Example 2 85 The P9C6 alloy showed a high thermal conductivity of more than 25 A / m after annealing. H c The example samples with an iron content not exceeding 85 at.%, namely Fe82.5 P 11.5 C6, Fe 83 P 11 C6, Fe 83.5 P 11 C6 and Fe 84 P 10.7 C 5.3 , their H c The values all did not exceed 8 A / m, which further proves that the super-tough Fe-PC amorphous soft magnetic alloy strip of the present invention has a lower coercive force value, and has significant advantages in improving the efficiency of electromagnetic equipment, reducing energy consumption, enhancing stability and expanding the scope of application, and thus is superior to the comparative example in performance.
[0035] Fe prepared in the example 82.5 P 11.5 C6, Fe 83 P 11 C6, Fe 83.5 P 11 C6 and Fe 84 P 10.7 C 5.3 The alloy exhibits excellent B s This may be attributed to the synergistic effect of two key factors: first, the lower metalloid content effectively curbs B s Secondly, the composition design with high Fe content promotes higher magnetic moment and better B s Performance.
[0036] In summary, the super-tough Fe-PC amorphous soft magnetic alloy ribbon prepared by the present invention exhibits the following significant advantages: 1. Optimization of alloy composition: By simplifying the alloy composition, mainly using P and C, avoiding the use of expensive elements such as Nb, effectively reducing costs; at the same time, the iron content is as high as 82 at.%, which not only improves the saturation magnetic induction intensity of the alloy to 1.60~1.68 T, but also makes the alloy surpass a variety of commercial iron-based alloys in magnetic properties. 2. Heat treatment optimization: The heat treatment temperature of the super-tough Fe-PC amorphous soft magnetic alloy ribbon prepared by the present invention is 5%~10% lower than the conventional one, and the processing time is shortened by 60%, which effectively prevents high-temperature embrittlement and improves production efficiency and material performance. 3. The simple preparation method gives the alloy excellent soft magnetic properties and plastic toughness, making it particularly suitable for the field of electronic power, which not only ensures the high performance of the material, but also ensures its wide applicability in actual production and application.
Claims
1. A super-tough Fe-PC amorphous soft magnetic alloy strip, characterized in that: The Fe-PC amorphous soft magnetic alloy ribbon is Fe x P y C z , x, y, z represent the atomic percentage of each element, 82<x<85, 8<y<12, 5<z<7, and x+y+z=100.
2. The super-tough Fe-PC amorphous soft magnetic alloy strip according to claim 1, characterized in that: 82.5≤x≤84。 3. The super-tough Fe-PC amorphous soft magnetic alloy strip according to claim 2, characterized in that: The Fe x P y C z Fe 82.5 P 11.5 C6, Fe 83 P 11 C6, Fe 83.5 P 11 C6 or Fe 84 P 10.7 C 5.3 .
4. The ultra-tough Fe-PC amorphous soft magnetic alloy strip according to claim 1, characterized in that: The thickness of the Fe-PC amorphous soft magnetic alloy strip is 23-26 μm.
5. A method for preparing the super-tough Fe-PC amorphous soft magnetic alloy strip according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) According to Fe x P y C z Make the batch with the ingredients shown; (2) The ingredients in step (1) are melted in an argon protective atmosphere, and after cooling, a master alloy ingot is obtained. The oxide scale on the surface is removed and the master alloy ingot is cut into pieces. (3) The spin-quenched alloy ribbon was prepared by single-roll rapid quenching method under argon atmosphere; (4) The spin-quenched alloy ribbon prepared in step (3) is subjected to vacuum annealing treatment at a temperature of 307-317° C. for a holding time of 10-15 min to obtain an ultra-tough Fe-PC amorphous soft magnetic alloy ribbon.
6. The method for preparing the super-tough Fe-PC amorphous soft magnetic alloy thin strip according to claim 5, characterized in that: The ingredients described in step (1) are Fe, Fe3P and C.
7. The method for preparing the super-tough Fe-PC amorphous soft magnetic alloy thin strip according to claim 5, characterized in that: In step (2), the smelting temperature is 1500-2000°C and the smelting time is 15-20 min.
8. The method for preparing the super-tough Fe-PC alloy thin strip according to claim 5, characterized in that: The operation method of the single-roll rapid quenching method in step (3) is: a small piece of master alloy ingot is placed in a quartz tube for melting treatment, and then the molten metal liquid is sprayed onto the surface of a high-speed rotating copper roller by using the spray pressure to rapidly cool it and form an alloy thin strip. In this process, the spray pressure is set to 0.02 MPa, the linear speed of the copper roller surface is 40 m / s, and the diameter of the small hole opened at the lower end of the quartz tube is 0.7~0.8 mm.
